Validity Evidence for a State-Specific Assessment of In-Session Counselor Empathy: The State-Empathic Concern Scale. (2nd October 2019) - Johnson, David A.; Karcher, Michael J.
Abstract: Many researchers assessing counselor empathy have inferred state-specific counselor empathy in a counseling session using trait empathy assessments. This article introduces the State-Empathic Concern Scale, a state-specific assessment of counselor empathy based on Davis's (1994) multidimensional empathy model. Results indicated moderate to strong evidence of construct validity among 200 counselors-in-training.